Managing A Case of Bilateral Congenitally Missing Maxillary Lateral Incisors by First Premolars Substitution and Ectopically Erupted Permanent Canines - A Case Report (Orthodontic Journal of Nepal, 2022)
Orthodontic treatment of cases with congenitally missing unilateral or bilateral lateral incisors is always challenging in terms of treatment planning. Space management of such cases which also present with retained primary canines mind boggle an orthodontist whether to close space orthodontically, or maintain the space and place prosthesis. Here we are presenting a case where space management of lateral incisors space has been done satisfactorily with teeth substitution and orthodontic treatment mechanics only.